Yogurt is Effective in Reduction of Fasting Blood Glucose Levels of Prediabetes in Employees - Rusana Rusana; Ida Ariani; Ahmad Subandi (GLOBAL HEALTH SCIENCE GROUP, 2020)
Prediabetes is a state of increasing a person's blood glucose level before become the Diabetes Mellitus or DM category. Untreated prediabetes, within 3-5 years can change to type 2 DM. Prediabetes blood glucose levels in the fasting state are 100-125 mg/ dL. The aim of this study was to determine the effectiveness of yogurt on 2 hours after meals blood glucose levels. The method used is quasi experiment pre and post test with control group. The total sample size is 30. The sampling technique is purposive sample. Data were collected by means of a questionnaire for the characteristics of respondents (sex, ages, Body Mass Index (IMT) and checking glucose levels. The data analysis using univariate analysis and independent t-test for bivariate analysis. The results of data analysis with independent-t showed a significant difference where respondents who were given yogurt experienced a decrease in 2 hours after meals/ PP blood glucose levels (p= 0,000). Blood glucose levels 2 hours after meals in respondents who were given yogurt in this study decrease/ lower (16%) than blood glucose levels 2 hours after meals on respondents who were not given yogurt.